Reading between the lines of the second-hand e-commerce business in China: A study of consumer behaviour Xianyu second-hand platform - SUN, Bing (Institutional Knowledge at Singapore Management University, 2023)
Second-hand transactions are gradually becoming an indispensable and significant form of the sharing economy; however, there is limited research on consumer behaviour in second-hand markets in an online environment. This dissertation aims to enrich the research in this area by analysing the impact of the characteristics of buyers, sellers, and products in second-hand markets on consumer purchasing intentions and behaviours. The study uses transaction data from Xianyu, China’s largest C2C second-hand trading platform, to investigate the factors that influence consumers’ choices between first-hand and second-hand trading platforms. It was found that consumers have a higher willingness to purchase well-known brands in second-hand platforms, and purchasing products with higher emotional value for consumers also increases the likelihood of choosing second-hand platforms. The study also examines the factors that influence consumer purchasing intentions in second-hand platforms and finds that seller characteristics, such as historical evaluation level and experience level, have a significant impact on buyers’ purchasing intentions. However, this impact is not constant and is subject to modulation by buyer-related characteristics. Moreover, we extracted features such as emotions, motives, and strategies from the chat conversations between buyers and sellers using natural language processing (NLP) methods and validated that these features significantly affect the transaction outcomes. This research is an empirical study covering the entire process of online second-hand transactions, analyzing the influences of user and product characteristics, providing theory guidance and practical reference for the operation of second-hand trading platforms and consumer behaviour within these platforms.